Praxis and the language of improvement: inquiry-based approaches to authentic improvement in Australasian schools. Issue 1 (2nd January 2016) - Groundwater-Smith, Susan; Mitchell, Jane; Mockler, Nicole
Abstract : In this paper, we explore the notion of school improvement through the lens of praxis as it relates to equity, inclusion, and transformation, with a particular focus on inquiry-based school and teacher development. We argue that authentic improvement is a consequence of praxis, and highlight, through examples, key ways that authentic school improvement might be achieved through inquiry within a praxis framework. While many recent policy initiatives related to school education in Australia, and internationally, place emphasis on competitive and performance-based mechanisms to drive improvement, the argument in this paper runs counter to these emphases, not in its recognition of the need for school improvement but in its understanding of how that improvement can be defined, developed, and documented. The examples presented illustrate ways in which inquiry-based approaches to teacher professional learning, and teaching practices in classrooms, provide tools for framing authentic school improvement.